Finanzierung von intelligenten Verkehrssystemen - Günter Knieps (Wirtschaftsdienst, 2017)
– Recently the importance of public investment in the EU digital internal market has been increasingly stressed. The paper analyses how government subsidies for ICT investments should be assessed from an economic point of view. The focus is on the limits of financing ICT via usage-dependent user fees in broadband communication systems and in global navigation satellite systems. Both have the character of a General Purpose Technology (GPT), and they form the basis for a multitude of applications that are important in the 'App economy'.
Keywords: L86; L88; L96; O31; 330